Two-pass dual-energy CT imaging for simultaneous detection, characterization, and volume measurement of urinary stones with excretory-phase CT urography alone: a phantom study. - Takahashi, Satoru; Itoh, Toshihide; Niikawa, Hidekazu; Shikata, Atsushi; Murakami, Emi; Tsunoda, Hiroshi; Yoshioka, Toshiaki; Tsujihata, Masao; Yamamoto, Hiroshi (Japanese Journal of Radiology, 2013)
Purpose: To evaluate if two-pass dual-energy CT imaging--i.e., simultaneous three-material and two-material decomposition analysis--can depict and characterize urinary stones in various concentrations of iodine solution in vitro.Materials and Methods: Twelve urinary stones were scanned with a dual-source CT scanner. First, each stone (in a saline-filled tube) underwent single- and dual-energy mode CT scans in order to measure the volume of the stone. Each stone was then placed in various concentrations of contrast medium and scanned in dual-energy mode to calculate its volume via three-material decomposition analysis. Two-pass dual-energy CT imaging analysis software for the Matlab environment, which was developed specifically to process simultaneous three-material and two-material decomposition, was applied to characterize and calculate the volume of each stone.Results: Although the virtual non-contrast images from three-material decomposition analysis clearly visualized all of the stones in contrast medium with up to 80 mgI/mL, the volumes of the uric acid stones were overestimated. Two-pass dual-energy CT imaging was able to depict and characterize non-uric-acid stones in diluted contrast medium with up to 80 mgI/mL, whereas uric acid stones were correctly evaluated in diluted contrast medium with 40 mgI/mL or less.Conclusions: Two-pass dual-energy CT imaging is able to depict and characterize urinary stones in contrast medium.